Challenges Faced by SMP Dharma Wanita 17 Wonoayu in the Implementation of Education Digitalization - Nadila Rizki Tri Rachmawati (Formosa Journal of Sustainable Research, 2023)
Technology and learning media are aspects that are quite important for now in the learning process in the 21st century. Where as is known, now technological developments have penetrated into almost all fields that are running in people's lives. One of them is education. The purpose of writing this article is to find out the challenges of implementing digitalization of education, especially at SMP Dharma Wanita 17 Wonoayu. The research method used in writing this article is a literature study supported by direct observation of the target schools. The research results obtained from writing this article are that there are several challenges in realizing the digitalization of education, especially at SMP Dharma Wanita 17 Wonoayu, including the low interest in student learning, then there are educators who are perceived to be technologically illiterate, then a lack of understanding of the importance of digitalization. education, and lastly is inadequate facilities